What’s in a name? An enquiry about the interpretation of Agama Hindu as “Hinduism” - Michel Picard (Pusat Kajian Bali Universitas Udayana, 2012)
AbstractIn this article, I question the conceptual categories of“religion”, “agama”, “dharma”, and “Hinduism”, in orderto investigate through which processes and within whichcontexts the Balinese religion resulted in being construedas agama Hindu. After having investigated how theSanskrit loanword agama came to designate in Indonesiaan Islamic conception of what “religion” is about, I assessthe similarities between the construction of Indian Neo-Hinduism and the interpretation of the Balinese religion asagama Hindu. In particular, I pay attention to the controversywhich has been dividing the Balinese intelligentsia overthe proper name of their religion, as it reveals a perennialconflict between the Balinese who want to retain thespecificity of their customary ritual practices, and thosewho aspire to reform the Balinese religion by conformingit to what they think Hinduism is about.